Metode Ekstraksi Minyak Gaharu-Analisis Bibliometrik Menggunakan VOSviewer - Saputra, Hendra; Satria, Benni; Nazir, Novizar; Anggraini, Tuty (DPPM Universitas Pelita Bangsa, 2024)
Agarwood is a non-timber forest product that has a very high selling value from Aquilaria and Gyrinops trees. Several terms for naming agarwood, in Southeast Asia, namely in the Middle East, it is called oud, in China chen xiang, in Japan Jinkoh and India agar. This research was carried out using a literature review approach by developing research questions and searching for articles using keywords on Scopus and Google Scholar using the Harzing's Publish or Perish application (Windows GUI Edition, Tarma Soft Ltd). A total of 300 articles were collected and 12 relevant articles were obtained. Then analysis was carried out using VOSviewer (Nees Java van Eck and Ludo Waltman). Various techniques have been used to extract various parts of agarwood, namely water distillation or hydrodistillation, steam distillation, solvent extraction, and supercritical fluid extraction. Optimization of agarwood oil extraction is carried out by pretreatment such as soaking with water, soaking with salt, fermentation with tempeh yeast, heating with a microwave and fermentation with Rhizopus sp. Several agarwood oil extraction techniques have been carried out to increase oil yield, namely multilevel maceration with various solvents, soxhletation, microwave hydrodistillation, accelerated solvent extraction. From the results of the literature review, maceration extraction with ethanol solvent for 72 hours showed the highest yield, namely 4.12%.